1998
DOI: 10.1161/01.str.29.11.2341
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Cerebral Dynamic Autoregulation From Spontaneous Fluctuations in Arterial Blood Pressure

Abstract: Background and Purpose-Assessment of cerebral autoregulation has been traditionally performed with static changes in arterial blood pressure. Newer dynamic methods require the induction of sudden drops in arterial blood pressure with the sudden release of bilateral thigh cuffs. An alternative method is proposed, based on the spontaneous variability of arterial blood pressure that does not require its manipulation. We compared this method with the established thigh cuff method in patients with carotid artery st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(167 citation statements)
references
References 29 publications
4
156
1
6
Order By: Relevance
“…Using standard procedures (Panerai et al 1998a, Zhang et al 1998, Panerai et al 1998b, Gommer et al 2010, Meel-van den Abeelen et al 2014b, Katsogridakis et al 2013, the coherence function, amplitude (gain) and phase frequency responses were calculated from the auto-and cross-spectra. The coherence function was visually inspected and TFA estimates were only accepted if the coherence was above 0.5 in the frequency range 0.15-0.25Hz where the BP-CBFV relationship can be assumed to be linear (Claassen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using standard procedures (Panerai et al 1998a, Zhang et al 1998, Panerai et al 1998b, Gommer et al 2010, Meel-van den Abeelen et al 2014b, Katsogridakis et al 2013, the coherence function, amplitude (gain) and phase frequency responses were calculated from the auto-and cross-spectra. The coherence function was visually inspected and TFA estimates were only accepted if the coherence was above 0.5 in the frequency range 0.15-0.25Hz where the BP-CBFV relationship can be assumed to be linear (Claassen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The autoregulation index (ARI) proposed by Tiecks et al (Tiecks et al 1995), usually obtained from thigh cuff manoeuvres (Tiecks et al 1995, Aaslid et al 1989, can also be derived by TFA (Panerai et al 1998b) and together with phase has been shown to be the most sensitive parameter to detect abnormalities in CBF regulation (Panerai 2008). Both the ARI and phase have been shown to have satisfactory, but not outstanding, reproducibility (Birch, Neil-Dwyer & Murrills 2002, Brodie et al 2009, Gommer et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Slow, synchronized waves of periods from 20 s to 2 min, as seen in FV, and traditionally used for the assessment of cerebral dynamic autoregulation using various models [9,[21][22][23], can also be observed in NIRS-derived TOI. Interestingly, such slow waves are usually not observed in directly measured brain tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral autoregulation can be understood as a self-defense mechanism against secondary ischemia, but also transmission of high blood pressure into the capillary bed. Impairment of autoregulation is found in a variety of diseases, such as head injury, ischemic stroke, and SAH [35]. In circumstances where autoregulation is impaired, changes in CPP or MAP may aggravate secondary brain injury, and this was found to be associated with poor outcome [15,25,36].…”
Section: Head Elevation and Cerebral Hemodynamicsmentioning
confidence: 99%